The Role of Manure, Nitrogen, Phosphorus and Potassium Fertilizer on Growth of Two Year Old Palm Oil in Jonggol, Bogor, Indonesia - Kanny, Putri Irene; Sudradjat, Sudradjat; Sugiyanta, Sugiyanta (International Journal of Sciences: Basic and Applied Research (IJSBAR), 2015)
Indonesia is the first producer of oil palm in the world, followed by Malaysia and Thailand. The development of oil palm plantations in Indonesia today, has been more difficult due to limited of fertile land. To improve soil fertility, the use of organic and inorganic fertilizers become a key factor of success for the development of oil palm plantations. The objectives of this research were to study the role and to determine the best fertilizer package of manure, nitrogen, phosphorus, potassium on growth of morphological and Physiological parameteres of two year old oil palm. The research was conducted at IPB-Cargill Teaching Farm Jonggol,